Falls, frailty, and metabolic syndrome in urban dwellers aged 55 years and over in the Malaysian elders longitudinal research (MELoR) study - a cross-sectional Study. Issue 3 (3rd April 2021) - Teoh, Ru Jian Jonathan; Mat, Sumaiyah; Khor, Hui Min; Kamaruzzaman, Shahrul Bahyah; Tan, Maw Pin
ABSTRACT: Objectives: While metabolic syndrome, falls, and frailty are common health issues among older adults which are likely to be related, the potential interplay between these three conditions has not previously been investigated. We investigated the relationship between metabolic syndrome with falls, and the role of frailty markers in this potential relationship, among community-dwelling older adults. Methods: Data from the first wave Malaysian Elders Longitudinal Research (MELoR) study comprising urban dwellers aged 55 years and above were utilized. Twelve-month fall histories were established during home-based, computer-assisted interviews which physical performance, anthropometric and laboratory measures were obtained during a hospital-based health check. Gait speed, exhaustion, weakness, and weight loss were employed as frailty markers. Results: Data were available for 1415 participants, mean age of 68.56 ± 7.26 years, 57.2% women. Falls and metabolic syndrome were present in 22.8% and 44.2%, respectively. After adjusting for age, sex, and multiple comorbidities, metabolic syndrome was significantly associated with falls in the sample population [odds ratio (OR): 1.33, 95% confidence interval (CI): 1.03; 1.72]. This relationship was attenuated by the presence of slow gait speed, but not exhaustion, weakness, or weight loss. Conclusion: Metabolic syndrome was independently associated with falls among older adults, and this relationship was accounted for by the presence of slow gait speed. Future studies should determine the value of screening for frailty and falls with gait speed in older adults with metabolic syndrome as a potential fall prevention measure.